Promoting aggregative competence through the production of a documentary: An intervention experience in Eastern Rome - Donatiello, Giuseppe; Vecchio, Cecilia (Quaderni di Psicologia Clinica, 2025)
The area of East Rome is characterized by a vibrant mix of gathering places (Arci clubs, concert halls, and self-managed spaces), which are very active in musical and cultural production. Therefore, this area became, over the past 15 years, a point of reference for the youth social aggregation of the city. As part of a project funded by Roma Capitale, Cras Psychology Studio – an agency focused on promoting systems of coexistence – partnered with Scomodo, an association engaged in youth aggregation and cultural production, carried out an initiative to explore the cultural dynamics that define this territory. The goal was to identify and share effective aggregation practices capable of fostering coexistence and a sense of belonging among citizens. “Key individuals” were interviewed; their narratives, collected through interviews and a focus group, were analyzed using a framework based on clinical psychological categories. The results reveal that the area’s aggregation practices tend to form as a reaction to contemporary consumer culture, within which social interaction often leads to the appropriation of local resources by both organizers and participants. A connection emerges between consumerist forms of aggregation and the need for social control. An alternative has been identified: the creation of contexts driven by the needs of the citizens and the issues of the area. In East Rome, both social isolation and the need to integrate socio-cultural differences are evident, along with a capacity for social aggregation that, if further recognized and supported, can respond effectively to these needs. The findings were disseminated through a documentary, designed to create opportunities for discussions on how aggregation can serve community development. Additional discussion sessions are currently planned.